When you are finding f(value), it just means you plug the value into the function and solve.
f(x) = 3x^2 + 9
f(-4) = 3(-4)^2 + 9
f(-4) = 3(16) + 9
f(-4) = 48 + 9
f(-4) = 57
2006-10-06 09:17:38
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
f(x)=3x^2+9
f(-4)=3(-4)^2+9
=3(16)+9
=48+9
=57
2006-10-10 03:15:35
·
answer #2
·
answered by srirad 2
·
0⤊
0⤋
57
2006-10-06 08:59:25
·
answer #3
·
answered by buccinator 3
·
0⤊
0⤋
57
2006-10-06 09:00:01
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
f(-4)=3(-4)^2+9=3*16+9=48+9=57.
2006-10-06 08:59:24
·
answer #5
·
answered by James L 5
·
1⤊
0⤋
for f(x)=....
x=-4 f(-4)=3*(-4)2+9=57
2006-10-06 09:31:02
·
answer #6
·
answered by Majdi B 3
·
0⤊
0⤋
57
Why?
Set x=-4
x^2=(-4)*(-4)=16
3x^2=3*16=48
3x^2+9=48+9=57
2006-10-06 09:00:07
·
answer #7
·
answered by Stuart T 3
·
0⤊
0⤋
f(x) = 3x^2 + 9
replacing x = -4 we get,
f(-4) = 3(-4)^2 + 9
f(-4) = 3*16 + 9
f(-4) = 48 + 9
f(-4) = 57
2006-10-06 09:02:02
·
answer #8
·
answered by aazib_1 3
·
0⤊
0⤋
201 I think. Oh, my bad, I was thinking it was -4 cubed. Yeah, 57.
2006-10-06 09:00:37
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
f(x)=3x^2+9
f(-4)=3(-4)^2+9
f(-4)=3*16+9
f(-4)=48+9=57
2006-10-06 10:08:24
·
answer #10
·
answered by yupchagee 7
·
0⤊
0⤋